Research developments in nanobiomaterials for tumor vaccines - Hengheng Dai; Weiwei Kong; Tingting Liu; Xiaoxia Fei (Medicine, 2026)
One of the most researched forms of tumor immunotherapy is tumor vaccines, which activate antigen-presenting cells (APCs) by administering adjuvants and tumor antigens, triggering an immune response against the tumor. Tumor growth is remarkably inhibited, and tumor metastasis and recurrence are prevented by tumor vaccines. However, to increase therapeutic benefit and ultimately improve the clinic, it is imperative to identify efficient delivery materials and mechanisms, as conventional tumor vaccines have shortcomings, such as low potency of their encapsulated antigens and a low ability to reach APCs. Numerous nanobiomaterials have the potential to significantly increase the efficacy of tumor vaccination, enhance their anti-tumor properties, and reduce the consequences of off-target effects. To promote the progress of nanobiomedicine in tumor immunotherapy and provide new perspectives for the design and implementation of tumor vaccine platforms, this article takes an in-depth look at the development of nanobiomaterials, including polymeric, lipidic, inorganic, and biomimetic nanomaterials.